2014
DOI: 10.1017/s1041610214000155
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of late-life depression: relationship with cognitive functioning

Abstract: Heterogeneity in late-life depression may lead to differences in cognitive functioning. Higher severity and having a first depressive episode was associated with worse cognitive performance. Additionally, different domains of cognitive functioning were associated with specific symptom dimensions. Our findings on the use of psychotropic medication suggest that close monitoring on cognitive side effects is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 34 publications
1
51
0
2
Order By: Relevance
“…Cognitive function is operationalized in four domains based on factor analyses in NESDO data (Korten et al, 2014) and displayed in Z scores. These four domains were interpreted as memory (immediate and delayed recall), processing speed (Stroop cards I and II), interference (interference score of the Stroop), and working memory (digit span forwards and backwards) (Klein et al, 1997).…”
Section: Other Characteristicsmentioning
confidence: 99%
“…Cognitive function is operationalized in four domains based on factor analyses in NESDO data (Korten et al, 2014) and displayed in Z scores. These four domains were interpreted as memory (immediate and delayed recall), processing speed (Stroop cards I and II), interference (interference score of the Stroop), and working memory (digit span forwards and backwards) (Klein et al, 1997).…”
Section: Other Characteristicsmentioning
confidence: 99%
“…Most likely, the association between executive functioning and physical frailty is lost due to the strong relationship between late-life depression and executive functioning. 12 On the other hand, we found a strong association of physical frailty with decreased verbal memory. Although population-based studies did not find this effect, a closer look at these studies showed that this might be due to a lack of statistical power in some studies.…”
Section: Comparison With the Literaturementioning
confidence: 50%
“…From these 3 cognitive tasks, 4 cognitive domain scores were created by means of factor analyses. 12 For all 4 domains, higher scores represent better cognitive functioning. The first domain, verbal memory, comprised the delayed recall task of a modified version of the Rey Auditory Verbal Learning Test.…”
Section: Cognitive Functioningmentioning
confidence: 99%
See 2 more Smart Citations